The association between disability and risk of exposure to peer cyber victimisation is moderated by gender: Cross-sectional survey. Issue 1 (January 2022) - Emerson, Eric; Aitken, Zoe; King, Tania; Arciuli, Joanne; Llewellyn, Gwynnyth; Kavanagh, Anne M.
Abstract: Background: Little is known about the exposure of youth with disability to cyber victimisation. Objective: /Hypothesis: To estimate the prevalence of peer cyber and non-cyber victimisation in a nationally representative sample of 14-year-old adolescents with and without disability and to determine whether gender moderates the relationship between disability and exposure to victimisation. Methods: Secondary analysis of data collected in Wave 6 of the UK's Millennium Cohort Survey on 11, 726 14-year-old adolescents living in the UK. Results: Adolescents with disability had higher prevalence of cyber and non-cyber victimisation than those with no disability. For cyber victimisation there was a statistically significant interaction between gender and disability, with evidence of increased cyber victimisation for adolescents with disability compared to those with no disability among girls, but not boys. For non-cyber victimisation there was no evidence of an interaction between gender and disability. Conclusions: The prevalence of both cyber and non-cyber victimisation was higher among adolescents with disability than those with no disability. The association between disability and risk of exposure to peer cyber victimisation appears to be moderated by gender.